(untitled) (Dhaka University Journal of Biological Sciences, 2019)
Twelve species of fungi, namely Aspergillus flavus Link., A. fumigatus Fresenius., A. niger van Tiegh (Type-I)., A. niger van Tiegh (Type-II), Chaetomium globosum Kunze ex Fr., Curvularia lunata (Wakker) Boedijn, Fusarium moniliforme var. subglutinans Wr. & Reink, F. sporotrichioides Sherb., Mem., Penicillium Link., Pestalotiopsis guepinii (Desm.) Stay., Rhizoctonia solani J.G. Kühn, Rhizopus stolonifer (Ehrenb.: Fr.) Vuill and Trichoderma viride Pers were isolated from the seeds of three cotton varieties (HC-1, HC-2 and HC-3) following “Tissue planting” and “Blotter” methods. Among the isolated fungi, six, namely A. flavus, A. niger, C. lunata, F. moniliforme var. subglutinans, F. sporotrichioides and Rhizoctonia solani showed pathogenic potentiality following seed inoculation technique. These pathogenic fungi had remarkable effect on seed germination, root shoot length and mortality of cotton seedlings. Dhaka Univ. J. Biol. Sci. 28(2): 187-193, 2019 (July)